Lithium supplement agent and preparation method thereof, positive pole piece, battery and electric equipment
By synergistically regulating Al doping and carbon coating, a lithium replenishing agent with high conductivity and air stability was prepared, solving the problems of poor conductivity and easy gas generation in the existing technology, and improving the energy density and cycle life of lithium-ion batteries.
Patent Information
- Application Number
- CN202511297274.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-11
- Publication Date
- 2026-01-09
AI Technical Summary
Existing positive electrode lithium replenishment agents suffer from poor conductivity, easy gas generation, and insufficient air stability, making it difficult to meet the requirements of high energy density lithium-ion batteries.
By employing the synergistic regulation of Al doping and carbon coating structure, and by adjusting the mass ratio of Al (A/I) and the ratio of ID/IG in the Raman spectrum, a lithium supplement with high conductivity and air stability was prepared.
The structure, conductivity, and air stability of the lithium replenishing agent were optimized, effectively suppressing gas generation during the delithiation process and improving the energy density and cycle life of the battery.
Smart Images

Figure BDA0005592763330000141 
Figure BDA0005592763330000151
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology and relates to a positive electrode lithium replenishing agent and its preparation method, a positive electrode sheet, a battery, and an electrical device. Background Technology
[0002] With the rapid development of the new energy field and the continuous improvement of people's living standards, the requirements for the driving range and lifespan of digital devices and electric vehicles are becoming increasingly stringent. Therefore, improving the energy density and cycle life of lithium-ion batteries is a research hotspot in the battery field. Lithium-ion consumption is a major cause of battery capacity decay, especially during the first charge and discharge process. The formation of an SEI film on the negative electrode surface by the electrolyte consumes a large amount of active lithium, leading to irreversible capacity loss.
[0003] Lithium replenishment is an important method for adding extra active lithium to lithium-ion batteries to offset the energy density decay caused by the depletion of active lithium. Conventional lithium replenishment methods include negative electrode replenishment and positive electrode replenishment. Negative electrode replenishment requires the use of n-butyllithium or lithium metal, which is more difficult and dangerous, hindering industrial application. Positive electrode replenishment involves adding a compound that easily delithiates under high voltage to the positive electrode; its use is relatively safe and facilitates industrial application.
[0004] Currently used cathode lithium supplements include Li5FeO4, Li2NiO2, Li6CoO4, and Li2O2, which generally suffer from poor conductivity. For example, Li5FeO4 has a very low conductivity of only 10⁻⁶. -9 The S / cm scale makes it difficult for the material to fully utilize its lithium replenishment characteristics. It also has problems such as poor environmental tolerance of the lithium replenishment agent, easy absorption of moisture, high residual alkali content, and high gas production. Summary of the Invention
[0005] This application provides a lithium replenishing agent and its preparation method, a positive electrode sheet, a battery, and an electrical device. The lithium replenishing agent provided by this application has a high lithium replenishing capacity, while also effectively suppressing gas production and exhibiting good conductivity and air stability.
[0006] The first aspect of this application provides a lithium replenishing agent, comprising a lithium replenishing core and a carbon coating layer covering the surface of the lithium replenishing core, wherein the lithium replenishing core is doped with Al; the lithium replenishing agent satisfies 0.3≤A / I≤4, where A is the mass percentage of Al in the lithium replenishing agent and I is the value of ID / IG in the Raman spectrum of the lithium replenishing agent.
[0007] The lithium supplement agent proposed in the first aspect of this application can effectively suppress gas production and has good conductivity and air stability through the synergistic regulation of Al doping amount and carbon coating layer structure.
[0008] A second aspect of this application provides a method for preparing the positive electrode lithium supplement agent as described above, comprising the following steps:
[0009] A first raw material system, including a first metal source and an aluminum source, is co-precipitated in a solvent to obtain a lithium-replenishing core precursor. The first metal source includes at least one of iron source, nickel source, manganese source, copper source, zinc source, cobalt source, chromium source, zirconium source, antimony source, titanium source, vanadium source, molybdenum source, and tin source.
[0010] A lithium source and the lithium-replenishing core precursor are mixed, ball-milled, and calcined to obtain a lithium-replenishing core.
[0011] The lithium replenishing core and carbon source are mixed and then carbon-coated to obtain a lithium replenishing agent.
[0012] The preparation method provided in this application combines aluminum doping and carbon coating. By adjusting the doping and coating processes, the key parameter A / I can be controlled, thereby preparing an Al-doped lithium supplement with a designable carbon coating layer. This supplement can effectively suppress gas generation, has good conductivity and air stability, and the process is simple and easy to mass-produce.
[0013] A third aspect of this application provides a positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, wherein the positive active material layer comprises the lithium supplement agent as described above. The positive electrode sheet provided by this application has high capacity and good stability.
[0014] This application provides a battery in a fourth aspect, comprising the positive electrode sheet described in the third aspect, the lithium replenishing agent described in the first aspect, or the lithium replenishing agent prepared according to the preparation method described in the second aspect. The battery provided by this application has a high energy density.
[0015] This application provides a fifth aspect of an electrical device, comprising the lithium replenishing agent described in the first aspect, the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect. The electrical device provided by this application exhibits excellent electrochemical performance. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0017] In related technologies, during the first cycle of a lithium-ion battery, a solid electrolyte interphase (SEI) forms at the negative electrode interface. This process is accompanied by irreversible lithium-ion consumption, significantly reducing the battery's initial coulombic efficiency and energy density. To compensate for this loss, lithium replenishing agents are introduced as additives to the positive electrode active material to improve the overall battery performance. However, lithium-rich lithium iron phosphate (such as Li5FeO4), commonly used as a lithium replenishing agent in existing technologies, suffers from lattice instability, leading to oxygen generation during delithiation and causing gas production in the battery, thus affecting battery safety and cycle life.
[0018] Furthermore, existing lithium replenishing agents exhibit severe side reactions with the electrolyte, further exacerbating the decline in battery performance. Although existing technologies have attempted to improve the conductivity and stability of materials through carbon coating, the structural design of the carbon coating layer lacks systematic control, resulting in significant differences in performance aspects such as powder resistance, moisture absorption rate, residual alkali content, and delithiation capacity, making it difficult to meet the multi-dimensional requirements of high-performance lithium-ion batteries for lithium replenishing agents.
[0019] In existing technologies, there is limited research on the synergistic regulation of Al doping amount and carbon coating layer structure, resulting in poor performance of lithium supplementation agents in terms of structural stability, conductivity, and air stability. In particular, when the A / I value (the ratio of Al element mass percentage to ID / IG value in Raman spectroscopy) is not effectively controlled, it is difficult to simultaneously optimize the gas generation suppression performance, conductivity, and air stability of lithium supplementation agents, thus limiting their application in high-energy-density lithium-ion batteries.
[0020] Based on this, this application provides a positive electrode lithium replenishing agent, which includes a lithium replenishing core and a carbon coating layer covering the surface of the lithium replenishing core. The lithium replenishing core is doped with Al element. The lithium replenishing agent satisfies 0.3≤A / I≤4, where A is the mass ratio of Al element in the lithium replenishing agent and I is the value of ID / IG in the Raman spectrum of the lithium replenishing agent.
[0021] In this application, the displacement range of peak D is generally 1350–1370 cm. -1 The displacement range of the G peak is generally 1560–1580 cm. -1 Among them, the G peak is the sp peak of carbon. 2 Hybridization peaks are mostly emanating from bulk carbon, which refers to carbon atoms within the carbon crystal that are saturatedly paired. More bulk carbon indicates a higher degree of graphitization in the carbon coating, larger sheets, greater two-dimensional planar spread, and higher conductivity. However, excessively large sheets hinder the densification of carbon materials on the surface of the lithium-filled core. The D peak represents edge carbon and sp... 3The peaks emitted by hybrid carbon are as follows: edge carbon refers to the carbon at the edge of the carbon crystal, which is surrounded by unsaturated pairs. The higher the intensity of the D peak, the higher the degree of disorder of the carbon material, indicating that the carbon material is more inclined to a point structure. The smaller the lamellar, the more conducive it is to the densification of carbon material on the surface of the lithium core. However, if the degree of disorder is too high, it is not conducive to the carbon coating layer to exert good conductivity.
[0022] Furthermore, Al doping in the lithium replenisher can suppress lattice distortion, improve the degree of side reactions with the electrolyte, and avoid severe gas generation.
[0023] This application defines the ratio of Al doping amount to ID / IG value as the structural stability index A / I of the lithium replenisher, which can be used to represent the structural stability of the lithium replenisher under the strategy of simultaneous doping and coating modification. Generally speaking, a high A / I value indicates a relatively large Al doping amount and a relatively small ID / IG value, indicating that the lithium replenisher core lattice is stable, the outer carbon coating layer has a high degree of graphitization, and the structure is dense with excellent conductivity. In this case, the lithium replenisher has a high degree of structural stability and usually has better gas generation suppression performance, conductivity, and air stability. A low A / I value indicates a relatively small Al doping amount and a relatively large ID / IG value, indicating that the lithium replenisher core may undergo excessive delithiation, the outer carbon coating layer has a low degree of graphitization, many structural defects, and poor conductivity. In this case, the lithium replenisher has a low degree of structural stability and usually has poor gas generation suppression performance, conductivity, and air stability. When the A / I value is too high, the lithium replenisher structure is too stable, making it difficult to delithigate Li5FeO4 and resulting in poor lithium replenishment. When the A / I value is too low, the lithium replenisher has many defects in the carbon coating layer, resulting in poor conductivity and air stability, and is prone to excessive delithiation, leading to severe gas generation. By adjusting the Al doping amount and the A / I ratio of the carbon coating layer structure, the structural stability, conductivity, and air stability of the lithium replenisher are ensured, while effectively suppressing gas generation during the delithiation process.
[0024] Optionally, A / I can be 0.3, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, or any value between any two of the above values.
[0025] In one embodiment, the lithium supplement satisfies 1 ≤ A / I ≤ 2. When A / I is within this range, it can balance structural stability and electrochemical performance, enabling the lithium supplement to maintain excellent conductivity while keeping the gas production rate low.
[0026] In one embodiment, 0.4 ≤ I ≤ 2. By controlling the peak intensity IG of the G peak and the peak intensity ID of the D peak in the Raman spectrum of the positive electrode lithium supplement, a suitable amount of highly graphitized bulk carbon and highly disordered edge carbon are distributed on the surface of the lithium supplement core, forming a dense, uniform, and highly conductive carbon coating layer. Optionally, I can be selected as 0.4, 0.6, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, or any value between any two of the above.
[0027] In one embodiment, the mass percentage of Al in the lithium supplement is 0.6% ≤ A ≤ 3%, preferably 0.8% ≤ A ≤ 2.5%. By controlling the Al doping amount, lattice structure instability can be effectively suppressed, while avoiding the decrease in conductivity caused by excessive Al, thus achieving synergistic optimization of structural stability and electrochemical performance. Optionally, A can be 0.6%, 1%, 1.5%, 2%, 2.5%, 3%, or any value between any two of the above.
[0028] In one embodiment, the chemical composition of the lithium-supplemented core is Li. a M b O c M includes one or more of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn, where 1 < a ≤ 8, 0 < b ≤ 1, and 0 < c < 7. This scheme, by flexibly selecting the type and ratio of element M, can adapt to the lithium replenishment performance requirements of different battery systems.
[0029] In one embodiment, the lithium-replenishing core comprises Al-doped Li5FeO4. This application uses lithium-rich lithium iron ferrite as the lithium-replenishing core, improving its structural stability through Al doping, and simultaneously enhancing its structural stability, conductivity, and air stability through carbon coating.
[0030] A second aspect of this application provides a method for preparing the positive electrode lithium supplement agent as described above, comprising the following steps:
[0031] A first raw material system, including a first metal source and an aluminum source, is co-precipitated in a solvent to obtain a lithium-replenishing core precursor. The first metal source includes at least one of iron source, nickel source, manganese source, copper source, zinc source, cobalt source, chromium source, zirconium source, antimony source, titanium source, vanadium source, molybdenum source, and tin source.
[0032] A lithium source and the lithium-replenishing core precursor are mixed and calcined to obtain a lithium-replenishing core.
[0033] The lithium replenishing core and carbon source are mixed and then carbon-coated to obtain a lithium replenishing agent.
[0034] The above method synthesizes the precursor through co-precipitation, ensuring a uniform distribution of doping elements. Calcination optimizes the lattice structure of the lithium-filled core; preferably, calcination follows ball milling. Carbon coating is achieved by controlling the ID / IG value of the carbon layer through adjusting the type of carbon source and process parameters, thus allowing for customized design of the coating layer structure. This method is efficient, convenient, and conducive to industrial production.
[0035] In some embodiments, the first raw material system further includes NH4HCO3; and / or, the solvent includes water. This approach effectively controls the precursor morphology by introducing ammonium bicarbonate as a precipitant, while water as a solvent offers advantages such as low cost and environmental friendliness.
[0036] In some embodiments, the aluminum source includes at least one of alumina, aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum isopropoxide, aluminum acetylacetonate, aluminum hydroxide, aluminum acetate, sodium aluminate, aluminum phosphate, aluminum oxide, aluminum hydroxide, and aluminum chloride; and / or, the iron source includes at least one of ferric chloride, magnetite, ferric oxide, ferric hydroxide, ferric hydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate, and ferric formate; and / or, the lithium source includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate, and lithium phosphate; the carbon source includes at least one of glucose, sucrose, citric acid, polyvinylpyrrolidone, chitosan, phenolic resin, lignin, polyacrylonitrile, pitch, carbon black, carbon nanotubes, and graphene oxide. This approach, through the diverse selection of raw materials, can adapt to different process conditions and performance requirements. For example, when glucose is used as a carbon source, a dense carbon layer can be formed through high-temperature carbonization, while graphene oxide can improve conductivity.
[0037] In some embodiments, calcination includes a first calcination and a second calcination; the temperature of the first calcination is 200-400℃, and the time is 1-5 hours; the temperature of the second calcination is 500-900℃, and the time is 8-15 hours. This scheme uses a segmented calcination process, first removing organic components from the precursor through the first calcination, and then forming a stable crystal structure through high-temperature sintering in the second calcination, avoiding material decomposition caused by local overheating. Optionally, the first calcination temperature can be selected as 200℃, 250℃, 300℃, 350℃, 400℃, or any value between any two of the above values; the first calcination time can be selected as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or any value between any two of the above values; the second calcination temperature can be selected as 500℃, 600℃, 700℃, 800℃, 900℃, or any value between any two of the above values; the second calcination time can be selected as 8 hours, 10 hours, 12 hours, 14 hours, 15 hours, or any value between any two of the above values.
[0038] Furthermore, the above calcination needs to be carried out in a protective atmosphere or an oxidizing atmosphere. The protective atmosphere includes any one or a combination of at least two of the following: nitrogen atmosphere, argon atmosphere, helium atmosphere, xenon atmosphere, radon atmosphere, neon atmosphere, or an argon-hydrogen mixture. The oxidizing atmosphere includes an oxygen atmosphere and / or an air atmosphere.
[0039] In some embodiments, the carbon coating process includes: ball milling, drying, and carbonizing the lithium core and the carbon source in a dispersant. This method achieves uniform mixing of the carbon source and the lithium core through ball milling, removes the solvent through the drying step, and uses high temperature to generate a coating layer in situ from the carbon source.
[0040] Specifically, the above calcination needs to be carried out in a protective atmosphere. The protective atmosphere includes any one or a combination of at least two of the following: nitrogen atmosphere, argon atmosphere, helium atmosphere, xenon atmosphere, radon atmosphere, neon atmosphere, or an argon-hydrogen mixture.
[0041] In some embodiments, the dispersant includes at least one selected from ethanol, N-methylpyrrolidone, ethylene glycol, isopropanol, acetone, tetrahydrofuran, dimethylformamide, cyclohexane, or ethyl acetate; and / or, the carbonization temperature is 400-900°C, and the time is 0.5-10 h. This method allows for the control of the dispersion of the carbon source on the lithium-filled core surface by selecting dispersants of different polarities, while the carbonization temperature and time directly affect the thickness and graphitization degree of the carbon layer. Optionally, the carbonization temperature can be selected from 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, and any value between any two of the above; the carbonization time can be selected from 0.5 h, 2 h, 4 h, 6 h, 8 h, 10 h, and any value between any two of the above.
[0042] In some embodiments, the first metal source in the first raw material system includes an iron source, with a molar ratio of Fe to Al of (7-19):(1-3); and / or, in the lithium replenishment core, the molar ratio of Li to Fe is (5-7):1; and / or, in the lithium replenishment agent, the molar ratio of Li to C is (89-99):(1-11). This scheme, by precisely controlling the element ratio, ensures that the stoichiometry of the lithium replenishment agent meets the design requirements, while avoiding performance degradation caused by excessive Li or C. Optionally, the molar ratio of Fe to Al can be selected as 7:1, 10:1, 13:2, 16:2, 19:3, or any value between any two of the above; the molar ratio of Li to Fe in the lithium-filled core precursor can be selected as 5:1, 6:1, 7:1, or any value between any two of the above; the molar ratio of Li to C in the lithium-filled core can be selected as 89:1, 92:4, 95:7, 98:10, 99:11, or any value between any two of the above.
[0043] A third aspect of this application provides a positive electrode sheet, including a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the lithium replenishing agent provided in the first aspect of this application.
[0044] Because the positive electrode sheet of this application includes the above-mentioned positive electrode lithium replenishing agent, it can exert excellent lithium replenishment effect and environmental stability when applied to batteries.
[0045] The positive current collector in this application can be selected from positive current collectors conventionally used in the art, such as aluminum foil.
[0046] In addition to the positive electrode lithium replenishing agent, the positive electrode active material layer of this application also includes components such as positive electrode active material, conductive agent and binder.
[0047] The positive electrode active material includes, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium nickel manganese oxide, and lithium-rich manganese-based materials.
[0048] Conductive agents include, but are not limited to, one or more of conductive carbon black, Super-C, acetylene black, Ketjen black, and carbon nanofibers.
[0049] The binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyvinylpyrrolidone, polytetrafluoroethylene, and styrene-butadiene rubber (SBR).
[0050] The more positive electrode lithium supplementer in the positive electrode active material layer, the better the lithium supplementation effect. However, excessive positive electrode lithium supplementer will inevitably lead to a decrease in the content of positive electrode active material, which is not conducive to improving the specific capacity of the positive electrode sheet and the energy density of the battery. Based on the above considerations, the mass content of positive electrode active material in the positive electrode active material layer should be controlled to be no less than 80%, and the mass content of positive electrode lithium supplementer should be less than 10%.
[0051] In one specific embodiment, the positive electrode sheet can be prepared by the following method: the positive active material, the positive lithium supplement, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive current collector. After drying, slitting and rolling, the positive electrode sheet can be obtained.
[0052] The fourth aspect of this application provides a battery, including the positive electrode sheet provided in the third aspect above. This battery can present various common structural forms, such as cylindrical batteries (e.g., 18650 and 21700 models, adapted for cylindrical casing, with the positive electrode sheet, negative electrode, and separator wound into a cell), prismatic batteries (including aluminum-cased prismatic and plastic-cased prismatic batteries, with the positive electrode sheet stacked or wound with other components and then installed in a prismatic casing), and pouch batteries (using aluminum-plastic film as the casing, with the positive electrode sheet flexibly adaptable to stacking or winding processes, suitable for lightweight applications), and can be selected with different capacities and sizes according to actual needs to adapt to diverse scenarios such as consumer electronics, new energy vehicles, and energy storage devices.
[0053] Furthermore, the battery of the fourth aspect of this application can also be a battery pack, i.e., multiple batteries connected in series, parallel, or a combination of series and parallel (e.g., using conductive connectors such as copper busbars or aluminum busbars for electrical connection), and combined with components such as a casing, circuit board, heat dissipation structure, and protection circuit to form a battery pack with specific voltage, capacity, and safety protection functions. The battery provided by the fourth aspect of this application has higher first-cycle coulombic efficiency and superior cycle performance during use.
[0054] In addition to the aforementioned positive electrode, the battery of this application also includes a negative electrode, an electrolyte, and a separator.
[0055] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector. The negative current collector can be selected from negative current collectors conventionally used in the art, such as copper foil. The negative active material layer can also refer to conventional compositions in the art; for example, the negative active material layer includes a negative active material, a conductive agent, and a binder. The negative active material can be selected from negative active materials conventionally used in the art, including, but not limited to, one or more of natural graphite, artificial graphite, silicon-carbon materials, silicon-oxygen materials, and hard carbon. The composition of the conductive agent and binder can refer to the types of conductive agents and binders used in the positive electrode sheet, and will not be elaborated here.
[0056] The function of the separator is to separate the positive and negative electrode plates, prevent them from contacting and short-circuiting, and allow lithium ions to pass freely. This application does not specifically limit the type of separator, which can be a porous separator with good chemical and mechanical stability commonly used in the art, including but not limited to one or more of polypropylene, polyethylene, glass fiber, and non-woven fabric.
[0057] An electrolyte is a medium existing between the positive and negative electrode plates for conducting lithium ions. It can be a gel, solid, or liquid electrolyte. This application does not specifically limit the type of electrolyte, which can be selected from gel, solid, or liquid electrolytes commonly used in the art.
[0058] In one specific embodiment, the battery of this application can be prepared by the following method: after stacking the positive electrode, separator and negative electrode in sequence, the battery cell is obtained by stacking or winding process, and then the battery of this application can be obtained by baking, liquid injection, formation and packaging processes.
[0059] The fifth aspect of this application provides an electrical device including the battery described above. This application does not specifically limit the type of electrical device; it can be any electrical device including the battery, including but not limited to mobile phones, portable devices, laptops, electric bicycles, electric vehicles, electric toys, energy storage devices, etc.
[0060] The following will provide a detailed description of the positive electrode lithium replenishing agent, its preparation method, and its application through specific embodiments.
[0061] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0062] Example 1
[0063] Ferric nitrate and aluminum nitrate (Fe:Al molar ratio 97:3) were dissolved in deionized water to form a 0.6 mol / L mixed solution. Excess NH4HCO3 was added for co-precipitation. The mixture was then centrifuged, washed, and dried to obtain the (Fe,Al)(OH)3 precursor. Subsequently, LiOH and the (Fe,Al)(OH)3 precursor were ball-milled together with a Li:Fe molar ratio of 5.5:1. The mixture was then calcined at 300℃ for 2 h in an oxygen atmosphere, followed by a second calcination at 760℃ for 10 h to synthesize Al-doped Li5FeO4. This Li5FeO4 powder was then pulverized into powder using an air jet (dew point below -40℃). The Li5FeO4 powder was ball-milled with citric acid in ethanol (Li:C molar ratio 94:6), spray-dried to form a spherical precursor, and carbonized at 500℃ for 9 h in an Ar atmosphere to form a continuous carbon layer. Finally, the target product was obtained by ball milling and sieving. Raman spectroscopy revealed an ID / IG value of 1.72.
[0064] The prepared Li5FeO4 lithium supplementer was uniformly mixed with conductive agents CNT, PVDF, lithium iron phosphate, and NMP in a ratio of 1.8:7:2.5:100:60. After being uniformly dispersed into a positive electrode slurry, it was uniformly coated onto an aluminum foil current collector, with a double-sided coating surface density of 434 g / m². 2 The positive electrode sheet is produced by rolling and die-cutting. Graphite material, conductive agent, and binder are dissolved and mixed evenly in deionized water at a ratio of 100:1:5 to prepare a negative electrode slurry. This slurry is then coated onto copper foil with a double-sided coating density of 210 g / m². 2After being rolled and die-cut, the negative electrode sheet is made. The positive electrode sheet, separator, and negative electrode sheet are stacked to form a 7+8 layer soft-pack cell, which is then packaged in an aluminum shell or aluminum-plastic film, baked, and injected with electrolyte to form a battery. The battery then undergoes formation, aging, and capacity testing to perform performance tests.
[0065] Example 2
[0066] The preparation method was basically the same as in Example 1, except that the carbon source was replaced with chitosan and the carbonization process was changed to carbonization at 600℃ for 5 hours. Raman spectroscopy yielded an ID / IG value of 1.38.
[0067] Example 3
[0068] The preparation method is basically the same as in Example 1, except that the carbon source is replaced with citric acid and the carbonization process is replaced with carbonization at 700℃ for 1.5h. Raman spectroscopy yielded an ID / IG value of 1.05.
[0069] Example 4
[0070] The preparation method was basically the same as in Example 1, except that the carbon source was replaced with sucrose and the carbonization process was changed to carbonization at 750℃ for 1 hour. Raman spectroscopy yielded an ID / IG value of 0.68.
[0071] Example 5
[0072] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 91:9, the carbon source was changed to citric acid, and the carbonization process was changed to carbonization at 500℃ for 9 hours. Raman spectroscopy yielded an ID / IG value of 1.72.
[0073] Example 6
[0074] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 91:9, the carbon source was changed to chitosan, and the carbonization process was changed to carbonization at 600℃ for 5 hours. Raman spectroscopy yielded an ID / IG value of 1.38.
[0075] Example 7
[0076] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 91:9, the carbon source was changed to citric acid, and the carbonization process was changed to carbonization at 700℃ for 1.5 h. Raman spectroscopy yielded an ID / IG value of 1.05.
[0077] Example 8
[0078] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 91:9, the carbon source was changed to sucrose, and the carbonization process was changed to carbonization at 750℃ for 1 hour. Raman spectroscopy yielded an ID / IG value of 0.68.
[0079] Example 9
[0080] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 88:12, the carbon source was changed to citric acid, and the carbonization process was changed to carbonization at 500℃ for 9 hours. Raman spectroscopy yielded an ID / IG value of 1.72.
[0081] Example 10
[0082] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was replaced with 88:12, the carbon source was replaced with chitosan, and the carbonization process was changed to carbonization at 600℃ for 5 hours. Raman spectroscopy yielded an ID / IG value of 1.38.
[0083] Example 11
[0084] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 88:12, the carbon source was changed to citric acid, and the carbonization process was changed to carbonization at 700℃ for 1.5 h. Raman spectroscopy yielded an ID / IG value of 1.05.
[0085] Example 12
[0086] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 88:12, the carbon source was changed to sucrose, and the carbonization process was changed to carbonization at 750℃ for 1 hour. Raman spectroscopy yielded an ID / IG value of 0.68.
[0087] Example 13
[0088] The preparation method was basically the same as in Example 1, except that the Fe:Al molar ratio was changed to 84:16, the carbon source was changed to citric acid, and the carbonization process was changed to carbonization at 700℃ for 1.5 h. Raman spectroscopy yielded an ID / IG value of 1.05.
[0089] Example 14
[0090] Nickel nitrate and aluminum nitrate with a Ni:Al molar ratio of 95.5:4.5 were dissolved in deionized water to form a 0.6 mol / L mixed solution. Excess NH4HCO3 was added for co-precipitation. After centrifugation, washing, and drying, the (Fe,Al)(OH)3 precursor was obtained. Subsequently, LiOH and the (Ni,Al)(OH)3 precursor were ball-milled together with a Li:Fe molar ratio of 5.5:1. The mixture was calcined at 450℃ for 5 h and then at 780℃ for 15 h under an oxygen atmosphere to synthesize Al-doped LiNiO2. The LiNiO2 powder was then pulverized into powder by air jet milling under dry air (dew point below -40℃). The LiNiO2 powder was ball-milled with citric acid in ethanol (Li:C molar ratio of 94:6), spray-dried to form a spherical precursor, and carbonized at 700℃ for 1.5 h under an Ar atmosphere to form a continuous carbon layer. Finally, the target product was obtained by ball milling and sieving. Raman spectroscopy showed that its ID / IG value was 1.05.
[0091] The prepared LiNiO2 lithium supplementer was uniformly mixed with conductive agents CNT, PVDF, lithium iron phosphate, and NMP in a ratio of 1.8:7:2.5:100:60. After being uniformly dispersed into a positive electrode slurry, it was uniformly coated onto an aluminum foil current collector, with a double-sided coating surface density of 434 g / m². 2 The positive electrode sheet is produced by rolling and die-cutting. Graphite material, conductive agent, and binder are dissolved and mixed evenly in deionized water at a ratio of 100:1:5 to prepare a negative electrode slurry. This slurry is then coated onto copper foil with a double-sided coating density of 210 g / m². 2 After being rolled and die-cut, the negative electrode sheet is made. The positive electrode sheet, separator, and negative electrode sheet are stacked to form a 7+8 layer soft-pack cell, which is then packaged in an aluminum shell or aluminum-plastic film, baked, and injected with electrolyte to form a battery. The battery then undergoes formation, aging, and capacity testing to perform performance tests.
[0092] Comparative Example 1
[0093] This embodiment provides a carbon-coated Li5FeO4 lithium supplement with a designable carbon layer. The preparation method is basically the same as in Example 1, except that the Fe:Al molar ratio is replaced with 88:12, the carbon source is replaced with citric acid, and the carbonization process is replaced with carbonization at 900℃ for 10 hours. Raman spectroscopy yielded an ID / IG value of 0.28.
[0094] Comparative Example 2
[0095] This embodiment provides a carbon-coated Li5FeO4 lithium supplement with a designable carbon layer. The preparation method is basically the same as in Example 1, except that the Fe:Al molar ratio is replaced with 98:2, the carbon source is replaced with phenolic resin, and the carbonization process is replaced with carbonization at 500℃ for 12 hours. Raman spectroscopy yielded an ID / IG value of 1.95.
[0096] Comparative Example 3
[0097] This embodiment provides a carbon-coated LiNiO2 lithium supplement with a designable carbon layer. Nickel nitrate and aluminum nitrate (Ni:Al molar ratio 96:4) are dissolved in deionized water to form a 0.6 mol / L mixed solution. Excess NH4HCO3 is added for co-precipitation. After centrifugation, washing, and drying, a (Fe,Al)(OH)3 precursor is obtained. Subsequently, LiOH and the (Ni,Al)(OH)3 precursor are ball-milled together with a Li:Fe molar ratio of 5.5:1. The mixture is then calcined at 450°C for 5 h in an oxygen atmosphere, followed by a second calcination at 780°C for 15 h to synthesize Al-doped LiNiO2. This is then pulverized into powder using an air jet (dew point below -40°C) under dry air. The LiNiO2 powder is ball-milled with citric acid in ethanol (Li:C molar ratio 94:6), spray-dried to form a spherical precursor, and carbonized at 850°C for 10 h in an Ar atmosphere to form a continuous carbon layer. Finally, the target product is obtained by ball milling and sieving. Its ID / IG value was found to be 0.38 by Raman spectroscopy.
[0098] Battery manufacturing
[0099] After the lithium replenishing agent prepared in the above examples and comparative examples is used as a positive electrode, it is assembled with a negative electrode, electrolyte and separator according to the following method to obtain a lithium-ion battery:
[0100] Positive electrode preparation: The prepared lithium supplement agent, conductive agents CNT, PVDF, lithium iron phosphate, and NMP were uniformly mixed in a ratio of 1.8:7:2.5:100:60. After being uniformly dispersed into a positive electrode slurry, it was uniformly coated onto an aluminum foil current collector, with a double-sided coating surface density of 434 g / m². 2 The positive electrode sheet is produced by rolling and die cutting.
[0101] Negative electrode preparation: Graphite material, conductive agent, and binder are dissolved and mixed evenly in deionized water at a ratio of 100:1:5 to prepare a negative electrode slurry. This slurry is then coated onto copper foil with a double-sided coating density of 210 g / m². 2 After being rolled and die-cut, it is made into a negative electrode sheet.
[0102] Battery preparation: The positive electrode, separator, and negative electrode are stacked to form a 7+8 layer soft-pack cell, which is then packaged in an aluminum shell or aluminum-plastic film, baked, and injected with electrolyte to form a battery. The electrolyte is 1 mol LiPF6 dissolved in a solvent with a mass ratio of DMC / EMC / DEC of 1:1:1.
[0103] Test case
[0104] The following performance tests were performed on the lithium supplements or prepared batteries of the above embodiments and comparative examples:
[0105] 1. Discharge capacity and DCIR
[0106] Test Method: After the prepared battery was left to stand at 25℃ for 4 hours, the first charge capacity test was performed. The test conditions were: charging at 0.1C to 4.55V, constant voltage charging to 0.025C to record the battery's charge specific capacity, standing for 10 minutes, discharging at 0.1C to 2.0V, and recording the discharge specific capacity. DCIR Test: Using the discharge capacity as the nominal capacity, the battery was charged at 0.3C to 50% SOC, left to rest for 10 minutes, and then discharged at 1.5C for 30 seconds. The DCIR was obtained by dividing the voltage difference before and after discharge by the current. The test results are shown in Table 1.
[0107] 2. Residual alkali content test
[0108] The lithium supplementing agent prepared in the above examples and comparative examples was thoroughly mixed and ground with polyvinylidene fluoride (PVDF) and carbon nanotubes at a mass ratio of 8:1:1. The resulting slurry was coated onto a 300mm*1000mm aluminum foil with a thickness of 200μm as the positive electrode material for lithium-ion batteries. The obtained positive electrode material was cut into 60mm*70mm positive electrode sheets, and the positive electrode sheets were placed in a constant temperature and humidity chamber with a humidity of 60% for 0, 5, and 10 minutes, respectively. The residual alkali content of the positive electrode sheets placed under different environments was tested.
[0109] Test method: Methanol was used as the solvent to dissolve the residual alkali on the surface of the positive electrode lithium supplement to obtain the test solution. Potentiometric titration was performed on the test solution using a 0.01M HCl standard solution to obtain the titration curve. The LiOH content in the positive electrode lithium supplement was then determined. The test results are shown in Table 1.
[0110] 3. Moisture absorption rate
[0111] Test method: 0.2 g of lithium supplement from the examples and comparative examples were taken and dried in a vacuum oven at (60±1)℃ and a relative vacuum of -100 Pa for 2 h. The samples were then placed in a constant temperature and humidity chamber at 30% humidity and 25℃ for moisture absorption rate testing, with a test interval of 10 min. The moisture absorption rate of the material was obtained according to the formula v=(m1-m2) / m1*t, where m1 and m2 are the mass of the material before and after the test, respectively, and t is the test interval time, which is 10 min here. The test results are shown in Table 1.
[0112] 4. ID / IG
[0113] Test method: Spectral data are obtained through Raman spectroscopy. Peaks are fitted to the D and G peaks, and their integrated intensities or peak heights are calculated. The ratio of the two is ID / IG.
[0114] 5. A / I
[0115] Test method: The aluminum doping amount was measured by ICP. The ratio of Al doping amount to ID / IG value was defined as A / I.
[0116] 6. Gas production during aging
[0117] Test method: The batteries prepared in each embodiment and the comparative example were subjected to formation after electrolyte injection by constant current charging at 0.05C for 2 hours and constant current charging at 0.2C for 3 hours to form an SEI film. Then, the batteries were further charged to 4.1V at 0.03C to allow the lithium replenishment agent to fully decompose and remove lithium. Finally, they were aged at 45°C for 48 hours. The gas production volume (ml) was measured using the water displacement method, and its ratio to the rated capacity was used to measure the gas production during aging (ml / Ah). The test results are shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] By comparing Examples 1-14 with Comparative Examples 1-3, it can be seen that when the lithium replenishing agent satisfies 0.3≤A / I≤4, the lithium replenishing agent has a higher specific capacity. At the same time, the moisture absorption rate, residual alkali content, DCIR of the battery cell, and gas production of the lithium replenishing agent are all at a relatively low level. Comparative Examples 1 and 3 have higher DCIR and lower specific capacity, while Comparative Example 2 has a higher gas production.
[0122] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A lithium supplement, characterized in that, It includes a lithium replenishing core and a carbon coating layer covering the surface of the lithium replenishing core, wherein the lithium replenishing core is doped with Al. The lithium supplement meets the requirement of 0.3 ≤ A / I ≤ 4. Wherein, A is the mass percentage of Al element in the lithium replenishing agent, and I is the value of ID / IG in the Raman spectrum of the lithium replenishing agent.
2. The lithium supplement agent according to claim 1, characterized in that, 1.0≤A / I≤2.
0.
3. The lithium supplement agent according to claim 1 or 2, characterized in that, 0.4% ≤ I ≤ 2%; and / or, 0.6% ≤ A ≤ 3%, preferably 0.8% ≤ A ≤ 2.5%.
4. The lithium supplement agent according to any one of claims 1-3, characterized in that, The chemical composition of the lithium-replenishing core is Li a M b O c M includes one or more of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn, where 1 < a ≤ 8, 0 < b ≤ 1, and 0 < c < 7.
5. The lithium supplement agent according to any one of claims 1-4, characterized in that, The lithium replenishment core comprises Al-doped Li5FeO4.
6. A method for preparing a lithium supplement, characterized in that, Includes the following steps: A first raw material system, including a first metal source and an aluminum source, is co-precipitated in a solvent to obtain a lithium-replenishing core precursor. The first metal source includes at least one of iron source, nickel source, manganese source, copper source, zinc source, cobalt source, chromium source, zirconium source, antimony source, titanium source, vanadium source, molybdenum source, and tin source. A lithium source and the lithium-replenishing core precursor are mixed and calcined to obtain a lithium-replenishing core. The lithium replenishing core and carbon source are mixed and then carbon-coated to obtain a lithium replenishing agent.
7. The preparation method according to claim 6, characterized in that, The first raw material system also includes NH4HCO3; and / or, The solvent includes water.
8. The preparation method according to claim 6 or 7, characterized in that, The aluminum source includes at least one selected from aluminum oxide, aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum isopropoxide, aluminum acetylacetone, aluminum hydroxide, aluminum acetate, sodium aluminate, aluminum phosphate, aluminum oxide, aluminum hydroxide, and aluminum chloride; and / or, The iron source includes at least one of ferric chloride, iron(II,III) oxide, ferric oxide, ferric hydroxide, ferric hydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate, and ferric formate; and / or, The lithium source includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate, and lithium phosphate. The carbon source includes at least one of glucose, sucrose, citric acid, polyvinylpyrrolidone, chitosan, phenolic resin, lignin, polyacrylonitrile, pitch, carbon black, carbon nanotubes, and graphene oxide.
9. The preparation method according to any one of claims 6-8, characterized in that, The calcination includes a first calcination and a second calcination; The first calcination temperature is 200-400℃, and the time is 1-5h. The second calcination temperature is 500-900℃, and the time is 8-15h.
10. The preparation method according to any one of claims 6-9, characterized in that, The carbon coating process includes: The lithium core and the carbon source are ball-milled, dried, and carbonized in a dispersant.
11. The preparation method according to claim 10, characterized in that, The dispersant comprises at least one of ethanol, N-methylpyrrolidone, ethylene glycol, isopropanol, acetone, tetrahydrofuran, dimethylformamide, cyclohexane, or ethyl acetate; and / or, The carbonization process is carried out at a temperature of 400-900℃ for 0.5-10 hours.
12. The preparation method according to any one of claims 6-11, characterized in that, The first metal source in the first raw material system includes an iron source, and the molar ratio of Fe to Al is (7-19):(1-3); and / or, In the lithium-replenishing core, the molar ratio of Li to Fe is (5-7):1; and / or, In the lithium replenishing agent, the molar ratio of Li to C is (89-99):(1-11).
13. A positive electrode plate, characterized in that, It includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the lithium supplement agent according to any one of claims 1-5 or the lithium supplement agent prepared by the preparation method according to any one of claims 6-12.
14. A battery, characterized in that, This includes the positive electrode sheet as described in claim 13, the lithium replenishing agent as described in any one of claims 1-5, or the lithium replenishing agent prepared by the preparation method according to any one of claims 7-13.
15. An electrical appliance, characterized in that, Includes the lithium replenishing agent according to any one of claims 1-5, the positive electrode sheet according to claim 13, or the battery according to claim 14.
Citation Information
Patent Citations
LATP-applied lithium ion battery positive electrode material and preparation method
CN111180703A
Lithium-rich iron-based composite material as well as preparation method and application thereof
CN115347187A
Lithium supplement agent suitable for high-voltage positive electrode as well as preparation method and application of lithium supplement agent
CN115863797A
Positive lithium supplement agent and preparation method thereof, positive pole piece, battery and electric equipment
CN119786602A
Positive electrode active material and preparation method therefor, positive electrode sheet, secondary battery, battery module, battery pack and electrical device
WO2023240613A1
Cited By
Modified lithium-rich lithium iron phosphate lithium supplement and preparation method, application, lithium supplement positive electrode and lithium ion battery
CN122393447A